Supervision of Hajj Guidance Groups in West Sumatra - Juli Darma Yanti; Febrian Andis (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
The purpose of this study was to find out the methods used by the Regional Office of the Ministry of Religion of West Sumatra Province in managing Hajj Guidance Groups and the challenges faced in implementing it. A qualitative methodology, in the form of a field survey with a descriptive focus, was used in this research. The research findings show that there are five steps of supervision in the monitoring system: planning, establishing measurement of activity implementation, comparing implementation with standards, analyzing deviations, and corrective action. The challenge faced by the Regional Office of the Ministry of Religion of West Sumatra Province in guarding Hajj Guidance Groups is that it is far from Hajj Guidance Groups and there are still group that violate the rules. In carrying out optimal supervision, the Regional Office of the Ministry of Religion cooperates with the local district or city Ministry of Religion, both in relation to Hajj Guidance Groups operational permits and in the operational activities itself.